2020
DOI: 10.5155/eurjchem.11.4.370-376.2048
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil compositions of Rosmarinus officinalis L. leaves growing in Mersin, Turkey

Abstract: This study reports on the chemical compositions of the essential oil of Rosmarinus officinalis L. (Rosemary) grown in Mersin, Turkey. The essential oil of rosemary was obtained by hydrodistillation method, and the yield of rosemary oil was found to be about 1.2 % (v:w). The hydrodistilled volatile oil was analyzed by gas chromatography and mass spectrometry techniques. Forty-five components were identified in the essential oil of R. officinalis, which represented 100% of the total essential oils. The oxygenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The ligands were synthesized according to a previously published method. 4, 29 1 mmol of aryl chloride (m-or pchlorobenzoyl chloride) dissolved in anhydrous acetone was added to the potassium thiocyanate solution (1.1 mmol) in anhydrous acetone and, then the resulting mixture was stirred under reflux for half an hour. After the mixture was cooled to room temperature, a diethylamine solution (1.1 mol) in anhydrous acetone was added dropwise over a period of 15-20 min.…”
Section: General Ligand Synthesismentioning
confidence: 99%
“…The ligands were synthesized according to a previously published method. 4, 29 1 mmol of aryl chloride (m-or pchlorobenzoyl chloride) dissolved in anhydrous acetone was added to the potassium thiocyanate solution (1.1 mmol) in anhydrous acetone and, then the resulting mixture was stirred under reflux for half an hour. After the mixture was cooled to room temperature, a diethylamine solution (1.1 mol) in anhydrous acetone was added dropwise over a period of 15-20 min.…”
Section: General Ligand Synthesismentioning
confidence: 99%
“…Olmedo et al found that camphor (35.70 g/100 g) was the most important component in REO, followed by verbenone (26.20 g/100 g) and b-caryophyllene (15.80 g/100 g) (24). In addition, another study showed that rosemary oil contains 45 volatile compounds, and eucalyptol (1,8-cineole) was the most abundant (33.15%), followed by camphor (10.31%), α-pinene (8.11%), isocaryophyllene (7.02%), bornyl acetate (5.66%), α-terpineol (4.92%), and camphene (4.22%), while differences in geographic location [30] may explain the differences between our study and previous studies. Generally, the natural antioxidant properties are mainly attributed to their phenolic contents; thus, their antioxidants action is like synthetic phenolic antioxidants [31].…”
Section: The Chemical Analysis and Identification Of Reo By Gc/msmentioning
confidence: 99%